Sound of millennia - Pacific Mountain Network (Seoul : Korea Foundation, 1992)
The Korean National Music Company presents a program of the performing arts of Korea, including vocal and instrumental music and dance. Both folk music and court music are represented, using the 5 or 7 note scales of Korean music
Title on container
H-71024
Copy available in DVD format
VHS format
Keywords: Music -- Korea; Dance -- Korea